Phil Donahue examines the human animal. - Brockway, Merrill; Donahue, Phil (Films for the Humanities, 1986)
Phil Donahue explores the human relationships of love and sex in various stages of life. Discusses what shapes a child as a sexual being. Examines the sexual behavior of today's teenagers and their attitudes toward love and sex. Discusses the marriage relationship, sexual problems, and the homosexual. Includes numerous comments from men, women, and teenagers, as well as research and commentary from experts.